Characterizing water quality datasets through multi-dimensional knowledge graphs: a case study of the Bogota river basin. Issue 2 (23rd February 2022) - Rondón Díaz, Juan D.; Vilches-Blázquez, Luis M.
Abstract: The world is transforming into a predominantly urban space, meaning that cities have to be ready to provide services, for instance, to ensure availability and sustainable management of water and sanitation for all. In this scenario, the water quality evaluation has a crucial role and often needs multiple sources segregated. Our purpose is to build bridges between these data silos to provide an integrated and interoperable view, where different datasets can be provided and combined through knowledge graphs in order to characterize water quality. This work shows the quality of the Bogota river basin's water bodies by analyzing physicochemical and biological properties using spatio-temporal and legal elements. So, our knowledge graphs allow us to discover what, when, and where infractions happened on water quality in a river basin of the most populated cities of Latin America during a critical period (2007–2013), highlighting the presence of high values of suspended solids and nitrites, lower amounts of dissolved oxygen, and the worst water quality during the driest periods (appearing until a maximum of 63 infractions in a year). HIGHLIGHTS: A new water quality ontology with three modules composed of diverse international standards. Multi-dimensional knowledge graphs about the water quality of the Bogota river basin were developed. The water quality characterization using spatio-temporal distribution and legal framework from an integrated and interoperable scenario. Graphical Abstract